Genital tumors in children and adolescents - Castellano, Carlos (2015)
We report 116 cases of benign and malignant tumors of the genital area of children and adolescents up to 17 years, diagnosed in a span of 19 years, from 1952 to 1971 at a single institution. These tumors are rare at this age, they constitute only 0.6%; instead, they are much more common in adult women after age 17, group forming 99.4% of our cases. Of the 116 cases more than a third they corresponded to the group of malignant and almost two-thirds have been benign. 40 cases of malignant tumors of OU casuistry, represent the biggest single resportada so far in series. The most common malignant tumors in childhood and adolescence are ovarian location, which representana more than two-thirds of the total, followed by vaginal location. We emphasize certain gynecological principles that guide the surgeon in the management of benign ovarian tumors in children and adolescents. Our series of gynecologic cancer is made up of 13,558 cases of malignancy in adult women, for only 40 cases in children and adolescents, equivalent in percentage to 99.8% and 0.2% respectively. It is interesting to note that the average age for malignant tumors of the vulva, uterus and ovary fluctuates around 12 years, whereas it is much less, 5.4 years for vaginal location. We present a case of malignant hemangiopericitoma of the vulva, which has not previously been reported.